Global Warming: Global warning for local actions - Abdul Malek (Syiah Kuala University, 2013)
After decades of global warming many are still in the dark as what needs to bedone to overcome this world threat that affects single citizen of the planet earth. The word ‘sustainability’ has been used very loosely, some not knowing the exact meaning of it only with intentions to gain research grant for the academics, profit making by keeping by the general business environment, thus leading to dumping the market with green-washing products. Those who seriously know the true meaning are not many and many times frustrated with the doings of the many which do not. This presentation hopefully providesome useful insights as to what sustainability means and for the necessary green initiatives that need to be taken to reduce further aggravation of the borderless geographical environment. Future growth in all countries are converging into a common trend and therefore efforts need to be in tandem and synchronized for a more effective win against this pervasive war of the world. Most tangible efforts are normally easily observed in the socio economic trend that affects the built environment of individual countries. The commoncues of the world are that it is getting hot, flat and crowded and to overcome this force is no easy task for any nation since the rhythm and tempo of growth of each nation differs. But one thing is common, that the rate of urbanization is rapid throughout the world. It was reported that by about 2030 the land-use for urbanization will be about 75% all over the world and so a relook at the socio economic policies must be geared towards how urbanization do not worsen the already bad situation from global warming.